Triumphs and failures of ordoliberalism: German flexicurity as a European development model - Cazorla Rodríguez, Marta (Papeles de Europa, 2019)
This study is an analysis of the flexicurity model, contextualizing it within the German ordoliberal tradition and its co-determination model. Its aim is to disentangle the complex factors that have contributed to the success and the failures of the structural reforms that took place in Germany in the beginning of this century. To do that we focus the analysis on its impact on a number of labour-related, social and macroeconomic variables. The data that the generalization of precarious employment has led to a dependency on external demand of the German economy, which has fostered an exports-led accumulation regime that exploits and worsens de divergences within the EMU.
Keywords: Economic policy; ordoliberalism; regulatory regimes; tripartite dialogue; co-management; foreign sector; Germany; UME